Application of FTIR Spectroscopy Combined with Multivariate Calibrations for Analysis of Chloramphenicol and Hydrocortisone Acetate in Cream Samples - Kusnul Khotimah; Sudibyo Martono; Anjar Windarsih; Irnawati Irnawati; Erna Prihandiwati; Abdul Rohman (Indonesian Journal of Pharmacy, 2021)
Analysis of chloramphenicol (CL) and hydrocortisone acetate (HCA) in cream samples using FTIR (Fourier Transform Infrared) spectroscopy. The objective of this study was to develop FTIR spectroscopy combined with multivariate calibrations for effective analysis of CL and HCA in cream formulation. High performance liquid chromatography (HPLC) method was applied for determining the actual value of CL and HCA. Cream samples containing CL and HCA were scanned using FTIR spectrophotometer employing attenuated total reflectance (ATR) technique. FTIR-ATR spectra were subjected to several optimization including wavenumbers selection and derivatization for quantitative analysis. The results showed that the optimum prediction model for correlation between actual values of CL and HCA as determined by HPLC and FTIR-predicted values was obtained using first derivative FTIR spectra at wavenumbers of 1500-1000 cm-1. The R2 value for calibration and internal validation for CL and HCA was > 0.9 with relatively small RMSEC (root mean square error of calibrations), RMSECV (root mean square error of cross validations) and PRESS (predicted residual error sum of squares) values. External validation of CL and HCA models produced R2 > 0.98 with RMSEP values of 0.6501 and 1.0041, respectively. The results of CL and HCA assay using HPLC and FTIR spectroscopy were compared resulting non-significant results (p > 0.05) for these two methods. FTIR spectroscopy in combination with PLS can be used as a rapid and reliable analytical method for determination of CL and HCA in cream formulation.